A Novel and Smart IoT System for Real Time Agriculture Applications with IaaS Cloud Computing - Thalluri, Lakshmi Narayana; Prasad Ayodhya, Jitendra; Anjaneya Prasad, T.B.; Raju, Ch. Yuva; Vadlamudi, SaiDivya; Babu, P. Bose (2020 International Conference on Computer Communication and Informatics (ICCCI), 2020)
In this paper, we have designed an IoT system for real time agriculture application with IaaS cloud architecture. Overall system design involves, preparation of six Wi-Fi enabled sensor nodes, design of server with In this agriculture sector, to improve the database including dedicated IP, for visualization we have designed an application with data processing ability, finally all section's are interfaced to create eventual agriculture IoT system. In the first phase, we have designed six Wi-Fi enabled sensor node's each node is connected with five sensor's i.e., temperature, humidity, pH, pressure and flow sensors. Each sensor is connected to ARM11 processor with 1GHz clock speed. In second phase, created server with predefined database. Database is generalized as a organizing the collection of data. This database which is created, only authorized persons are allowed to access the database. Database can be created by using the MySQL which is an oracle backed open source relational database The database management system(RDBMS). Database is mainly used for storing the corresponding output values which are obtained from the sensors and analyze the data for day by day. Server is a networked computer that can be run a database. Here the sever is a web server which is allocated with public IP (i.e., internet protocol) which website can host. IP is mainly two types public IP and private IP, here we are using public IP which can be accessed over the internet. Public IP is generally having unique address that can be allocated to a computing device. Web application is designed by using HTML (hypertext markup language) programming for creating web pages with text, images. PHP (hypertext preprocessor) it will be embedded in a HTML code and it can supported in a webserver. Here, using protocols are HTTP(hypertext transfer protocol) protocol it provides communication to the world wide web.